The Effect of Using LINE Webtoon as a Media in Reading Comprehension at Eleventh Grade of Senior High School Number 8 Jambi City - Tasha Annisa Putri; Wennyta Wennyta; Yanti Ismiyati (Universitas Batanghari Jambi, 2023)
This research aims to find out whether there is any effect of using LINE Webtoon as a media in reading comprehension of English students at eleventh grade of Senior High School Number 8 Jambi City. This type of research is a quasi-experimental with a total of population 292 people. Through simple random sampling technique, 37 students of Class XI IPA 2 were selected as the control class and 37 students of Class XI IPA 1 were selected as the experimental class. The technique of collecting data is distributing questions to research respondents. In this research, the data analysis technique was using t test on the Statistical Package for the Social Sciences (SPSS) for Windows version 25 program. The result of this research indicated that (1) students’ reading comprehension in English subject in experimental class taught using LINE Webtoon as a media obtained an arithmetic mean of 24.89; (2) students’ reading comprehension in English subject in control class taught by using LINE Webtoon as a media obtained an arithmetic mean of 16.65; (3) students’ reading comprehension in English subject taught using LINE Webtoon as a media in experimental class are higher than students’ reading comprehension in English subject taught by using LINE Webtoon as a media in control class with a value of Sig. 0.000 > 0.05. Furthermore, there is an effect on the use of LINE Webtoon as a media in learning students’ reading comprehension as evidenced by the increase in students’ learning outcomes.